Deep Neck Infection and Descending Mediastinitis as a Complication of Propionibacterium acnes Odontogenic Infection - Evgeni Brotfain; Leonid Koyfman; Lisa Saidel-Odes; Abraham Borer; Yael Refaely; Moti Klein (Case Reports in Infectious Diseases)
Propionibacterium acnes is an anaerobic, Gram-positive bacterium which causes numerous types of infections. Isolated Propionibacterium acnes deep neck infections are very rare. We present an interesting case of deep neck infection complicated by descending mediastinitis of isolated Propionibacterium acnes infection.